การพัฒนาแบบประเมินสมรรถนะวิสัญญีพยาบาล โรงพยาบาลราชวิถี THE DEVELOPMENT OF NURSE ANESTHETIST COMPETENCY SCALE, RAJAVITHI HOSPITAL - ใจพินิจ วิไลรัตน์; วิเศษฤทธิ์ วาสินี (วารสารวิจัยสุขภาพและการพยาบาล (วารสารวิทยาลัยพยาบาลบรมราชชนนี กรุงเทพ), 2016)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อพัฒนาแบบประเมินและทดสอบคุณภาพของแบบประเมินสมรรถนะวิสัญญีพยาบาล โรงพยาบาลราชวิถี แบ่งการศึกษาเป็น 2 ระยะ คือ ระยะที่ 1 การสร้างแบบประเมิน มี 2 ขั้นตอน (1) สังเคราะห์รายการสมรรถนะวิสัญญีพยาบาล โรงพยาบาลราชวิถี โดยทบทวนวรรณกรรมและสนทนากลุ่มผู้เชี่ยวชาญวิสัญญีพยาบาล จำนวน 10 คน (2) สร้างข้อรายการสมรรถนะวิสัญญีพยาบาล โรงพยาบาลราชวิถี โดยการกำหนดรายการสมรรถนะจากการทบทวนวรรณกรรมและผลการสังเคราะห์จากการสนทนากลุ่มผู้เชี่ยวชาญและวิเคราะห์หาคุณภาพของข้อรายการสมรรถนะด้วยการตรวจสอบความตรงตามเนื้อหาโดยผู้ทรงคุณวุฒิ จำนวน 5 คน นำผลที่ได้ไปสร้างแบบประเมินสมรรถนะวิสัญญีพยาบาล โรงพยาบาลราชวิถี จากนั้นนำไปทดลองหาความเที่ยงกับกลุ่มตัวอย่าง คือวิสัญญีพยาบาล โรงพยาบาลนพรัตนราชธานี จำนวน 21 คน ทดสอบความเที่ยงโดยใช้สูตรสัมประสิทธิ์แอลฟาครอนบาค ได้เท่ากับ .99 ระยะที่ 2 การทดสอบคุณภาพของแบบประเมิน โดยนำแบบประเมินไปทดลองใช้เพื่อดูความสอดคล้องของแบบประเมินแบบ 360 องศา จากวิสัญญีพยาบาล โรงพยาบาลราชวิถีจำนวน 55 คน นำมาทดสอบความสอดคล้องของแบบประเมินระหว่างกลุ่มด้วยสถิติ Intra-class correlation coefficient ผลการวิจัยพบว่าแบบประเมินสมรรถนะวิสัญญีพยาบาล โรงพยาบาลราชวิถี ประกอบด้วยสมรรถนะหลัก 8 ด้าน จำนวน 78 ข้อรายการ คือ 1) ด้านการปฏิบัติการพยาบาลวิสัญญี 24 ข้อ 2) ด้านการปฏิบัติการช่วยฟื้นคืนชีพระยะวิกฤตขั้นสูง 8 ข้อ 3) ด้านการบริหารยาระงับความรู้สึก 7 ข้อ 4) ด้านความสามารถกระทำหัตถการ 7 ข้อ 5) ด้านการใช้อุปกรณ์และเทคโนโลยีทางการแพทย์ 8 ข้อ 6) ด้านการใช้เทคโนโลยีสารสนเทศและการติดต่อสื่อสาร 8 ข้อ 7) ด้านการใช้หลักฐานเชิงประจักษ์ในการปฏิบัติการพยาบาลวิสัญญี 7 ข้อ 8) ด้านคุณลักษณะของพยาบาลวิสัญญี 9 ข้อ คุณภาพของแบบประเมินมีค่าดัชนีความตรงตามเนื้อหา .93 ค่าสัมประสิทธิ์ความเที่ยง .98 ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐานโดยรวมอยู่ในระดับมาก 3.97 - 4.09 และความสอดคล้องของการประเมินสมรรถนะวิสัญญีพยาบาลระหว่างกลุ่มมีค่าเท่ากับ .97 Abstract This research aimed at developing and testing psychometric properties of Nurse Anesthetist Competency Scale at Rajavithi Hospital. The study was divided into the following two phases. Phase 1: Development of an appraisal form involving the following two steps: (1) synthesis of a component and capacity list for nurse anesthetists by means of a literature review and focus group discussions with a group of ten expert nurse anesthetists and (2) compilation of a list of nurse anesthetist competencies of Rajavithi Hospital, determined by similarity of the lists discovered in the literature review and synthesis of the experts’ focus group discussion. Content validity of the list of competencies was judged by five qualified experts. Then, the results were used to create the Nurse Anesthetist Competency Assessment Scale of Rajavithi Hospital. The scale was then tested for reliability with 21 nurse anesthetists at Nopparat Ratchathani Hospital. Reliability was tested by using Cronbach’s Alpha Coefficient which was reported at .99. Phase 2 involved testing the scale’s quality by trial of the form to see consistency in the form in 360 decrees in 55 nurse anesthetists at Rajavithi Hospital. The findings revealed that the Nurse Anesthetist Competency Scale of Rajavithi Hospital comprised 8 core competencies with 78 items. The items were composed of the following: 1) 24 items on clinical anesthesia (2) 8 items on the operating range of crisis advanced resuscitation (3) 7 items on anesthesia management. (4) 7 items on intervention ability (5) 8 items on the use of medical equipment and technology (6) 8 items on the use of information technology and communications (7) 7 items on the use of evidence in nursing anesthesiology practices. (8) 9 items on the characteristics of nurse anesthetists. The scale had high content validity index at .93 and Cronbach’s Alpha Coefficient was reported at .98. Overall mean and standard deviation were high between 3.97 – 4.09 and consistency of the scale between groups was .97.